1976
DOI: 10.1111/j.1570-7458.1976.tb02600.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysones and Plant Growth Regulators Induce Solitarious Characters and Reduce Fertility in the Desert Locust

Abstract: When a zoo‐ecdysone (crustecdysone), a supposed phyto‐ecdysone (from leaves of Podocarpus gracilior), or a plant growth regulator (Alar® 85) were injected into newly ecdysed, gregarious, fourth‐ instar nymphs of the desert locust, Schistocerca gregaria (Forsk.), the morphometric ratios of the resulting adults were intermediate between the two extreme phases. In no case a complete transformation to the solitarious form was obtained. Only the plant growth regulator resulted in the sterility of the adults. The po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…A similar result was recorded for S. littoralis by the same PGR (Salama and El-Sharaby, 1972). El-Ibrashy et al (1976) injected Alar ® 85 into the newly moulted gregarious 4 th instar nymphs of the desert locust Schistocerca gregaria and recorded complete sterility (zero fertility) in the treated locust. Adding GA3 or ABA to a grass diet of A. elliotti significantly reduced the egg viability (Visscher, 1980).…”
Section: Ii22 Reduced Fertilitysupporting
confidence: 79%
“…A similar result was recorded for S. littoralis by the same PGR (Salama and El-Sharaby, 1972). El-Ibrashy et al (1976) injected Alar ® 85 into the newly moulted gregarious 4 th instar nymphs of the desert locust Schistocerca gregaria and recorded complete sterility (zero fertility) in the treated locust. Adding GA3 or ABA to a grass diet of A. elliotti significantly reduced the egg viability (Visscher, 1980).…”
Section: Ii22 Reduced Fertilitysupporting
confidence: 79%
“…Previous experimental findings indicated, however, that differences in the peak concentration may be most significant. It was shown that partial ablation of PG, presumably followed by a reduction of ecdysteroid titre, causes appearance of some gregarious features in the solitary hoppers (Ellis and Carlisle, 1961), and that injection of phytoecdysteroids into gregarious larvae leads to their partial conversion to the solitary phase (El-Ibrashy et al, 1976). Our data do suggest that gregarious phase is associated with a lower ecdysteroid titre than in the solitary phase but additional measurements under various experimental conditions are needed to prove the role of ecdysteroids in the control of locust phase dimorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Tawfik et al [158] showed that the titres of ecdysteroid in the haemolymph of the solitary and gregarious penultimate and last instar larvae of S. gregaria; the longer duration of the moult-inducing surge of ecdysteroid; and the frequently higher proportion of highly polar products distinguish the gregarious from solitary larvae of S. gregaria. On the other hand, it was shown that partial ablation of prothoracic (also called ventral) glands (PGs), after which it was presumed that there would be a reduction in the titre of ecdysteroid, causes the appearance of some gregarious features in solitary hoppers [20], and that injection of phytoecdysteroids into gregarious larvae leads to the appearance of some solitary characters [159].…”
Section: Ecdysteroids In Larvaementioning
confidence: 99%